Stocktheft in Kenya: patterns, drivers and challenges - Bunei, Emmanuel K. (Acta criminologica, 2018)
The purpose of this article is to present the current challenges impeding policing of livestock theft in Kenya and suggest future ways to tackle it. Though, attempts have been made to address the problem of stock theft, it remains one of the persistent crimes in Kenya. Specifically, less has been done to critically analyse policing challenges accompanying prevention of livestock theft. By use of documentary reviews and in-depth analysis of policy documents - the article provides a critical understanding of the persistence of stock theft from an East African country. The article highlights how social-cultural, demographic, economic and technological development mutually reinforces each other to promote and impede policing of livestock theft in Kenya specifically. The article concludes by suggesting that there is need for more integrate approach to understanding of livestock theft which can inform development of practical and relevant interventions that can address changing dynamics of livestock theft in Kenya and Africa in general.